2022
DOI: 10.3389/fpls.2022.995073
|View full text |Cite
|
Sign up to set email alerts
|

A 1-aminocyclopropane-1-carboxylic-acid (ACC) dipeptide elicits ethylene responses through ACC-oxidase mediated substrate promiscuity

Abstract: Plants produce the volatile hormone ethylene to regulate many developmental processes and to deal with (a)biotic stressors. In seed plants, ethylene is synthesized from 1-aminocyclopropane-1-carboxylic acid (ACC) by the dedicated enzyme ACC oxidase (ACO). Ethylene biosynthesis is tightly regulated at the level of ACC through ACC synthesis, conjugation and transport. ACC is a non-proteinogenic amino acid, which also has signaling roles independent from ethylene. In this work, we investigated the biological func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Loss of ACS2 activity intensifies NaCl-induced inhibition of root growth, with the mechanism involving ACC accumulation activating IAA conjugases GH3.5 and GH3.9, ultimately leading to decreased IAA levels and impaired root growth [93]. A recent study showed that the dipeptide of ACC causes ethylene responses by means of substrate promiscuity mediated by ACO [94].…”
Section: Acc Homeostasis and Its Signaling Functionmentioning
confidence: 99%
“…Loss of ACS2 activity intensifies NaCl-induced inhibition of root growth, with the mechanism involving ACC accumulation activating IAA conjugases GH3.5 and GH3.9, ultimately leading to decreased IAA levels and impaired root growth [93]. A recent study showed that the dipeptide of ACC causes ethylene responses by means of substrate promiscuity mediated by ACO [94].…”
Section: Acc Homeostasis and Its Signaling Functionmentioning
confidence: 99%
“…Loss of ACS2 activity intensifies NaCl-induced inhibition of root growth, with the mechanism involving ACC accumulation activating IAA conjugases GH3.5 and GH3.9, ultimately leading to decreased IAA levels and impaired root growth [93]. A recent study showed that dipeptide of ACC causes ethylene responses by means of substrate promiscuity mediated by ACO [94].…”
Section: Acc Homeostasis and Its Signaling Functionmentioning
confidence: 99%